2014
DOI: 10.1371/journal.pgen.1004132
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Metabolic Traits Reveals Novel Gene-Metabolite-Disease Links

Abstract: Metabolic traits are molecular phenotypes that can drive clinical phenotypes and may predict disease progression. Here, we report results from a metabolome- and genome-wide association study on 1H-NMR urine metabolic profiles. The study was conducted within an untargeted approach, employing a novel method for compound identification. From our discovery cohort of 835 Caucasian individuals who participated in the CoLaus study, we identified 139 suggestively significant (P<5×10−8) and independent associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 57 publications
(75 reference statements)
5
96
0
Order By: Relevance
“…In this diverse population, which includes~30 BXD strains (with only one strain overlapping with those in our study), 2-AA is diminished in cohorts with higher fasted glucose (Figure 5F), and the two are again negatively correlated (Figure S2E). Likewise, we observed the same trend in a human population study (Cohorte Lausannoise [CoLaus] study [Firmann et al, 2008]), in which we recently analyzed the spot urine samples of 835 middle-aged or elderly individuals (Rueedi et al, 2014). In this cohort, diabetic patients (Figure S2E) also displayed a marked decrease in 2-AA levels (Figure 5F).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…In this diverse population, which includes~30 BXD strains (with only one strain overlapping with those in our study), 2-AA is diminished in cohorts with higher fasted glucose (Figure 5F), and the two are again negatively correlated (Figure S2E). Likewise, we observed the same trend in a human population study (Cohorte Lausannoise [CoLaus] study [Firmann et al, 2008]), in which we recently analyzed the spot urine samples of 835 middle-aged or elderly individuals (Rueedi et al, 2014). In this cohort, diabetic patients (Figure S2E) also displayed a marked decrease in 2-AA levels (Figure 5F).…”
Section: Resultssupporting
confidence: 72%
“…Strikingly, we replicated this association between 2-AA and high glucose levels in a recent and completely independent metabolomic data set collected in the Hybrid Mouse Diversity Panel (Ghazalpour et al, 2014). Furthermore, and clinically relevant, we demonstrated in a human population-based sample, Co-Laus, that diabetic patients likewise have lower urinary levels of 2-AA (Rueedi et al, 2014). Thus, 2-AA levels are consistently linked to the diabetes status in both mice and humans, and in the BXDs we can unequivocally attribute a causal part of this variance to variants in Dhtkd1 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The locus associated with 1-ribosyl-imidazoleacetate included brain eQTLs for several genes, including NAPRT, which encodes an enzyme (nicotinate phosphoribosyltransferase) involved in transferring ribosyl groups 55 . The locus for N6-methyllysine includes brain eQTLs for the PYROXD2 gene, which has been associated with other metabolites (trimethylamine and dimethylamine) in previous studies 50,56,57 . The locus associated with N-acetylglutamate included a brain eQTL for the SLC13A3 gene that encodes sodium-dependent dicarboxylate cotransporter 3, which has been implicated as a transporter for N-acetylglutamate and for N-carbamoylglutamate, a drug used to treat N-acetylglutamate synthase deficiency 58 .…”
Section: Discussionmentioning
confidence: 94%
“…Just one example of the potential of this approach is provided by a GWAS--metabonomics study of metabolic traits associated with SNPs found in 835 Caucasian participants on the CoLaus study. [62] A key finding was of an association between urinary fucose levels and the presence of SNP rs492602 in the FUT2 gene, which encodes a fucosyltransferase enzyme. The FUT2 gene has already been associated with Crohn's disease, and it was proposed that elevated urinary fucose could be a biomarker for the dysbiosis associated with Crohn's disease, especially as fucose is known to influence human microbiome composition.…”
Section: Future Perspectivesmentioning
confidence: 99%